PERMASALAHAN ANAK USIA SEKOLAH DASAR PADA SEKOLAH DASAR NEGERI DI KABUPATEN LAMPUNG TENGAH - Ratna Widiastuti (Jurnal Evaluasi dan Pembelajaran, 2019)
The research aim was to map the problems of the elementary school. The research problem was the teacher’s difficulties to give the guidance and counseling’s servies for prevention function. The research design was a decription with survey research and the data collection was using questionnaire. The sample research were 100 teachers from first grude until sixth grade at Lampung Tengah elementory school . Based on analysid data, it was conclude that (1) Therre were some problems faced by at first grade until sixth grade of elementary school’s students, (2)Hiere were some problems faced by the lower class students that were not faced by higher class, (3)There were some problems faced by the higher class that were not faced by the lower class. Baced on the research conclution, the researcher adviced that[ (1) The teacher should give a tight superviser at the test and do the acfivity as the indicatur for student at study, and the teacher should develop the student.s empathy and give the model to give empathy ; (2) the parent should make on acessment for the children the respect their friends and give the model for plating the ethiquestte at social association by giving the model. (3) Headmaster school with teacher make school’s rules that was oriented to prevent the the problems at school such as cheating , damage yhe school grads, and diligent to study also apply the saiention. Keywords: Guidance and problems student elementary school